Versions of Domestic Violence and Child Abuse in Children’s Literature - Ασαργιώτη, Κάλλια (Education Sciences, 2024)
The purpose of this paper is to investigate the representations of domestic violence and child abuse in classic and modern books for children published in Greece and abroad. The contribution of classics to the definition of the subject, the criteria of writing books that thermalize domestic violence and child abuse and the limits of their realistic representation are examined in our study. The article exemplifies how classic books overcome the reader’s strict age limits. It also looks into the literary techniques authors resort to overcome pedagogical censorship. Finally, the representation of the above themes in classic and modern books are compared so as to detect the shifts in a given author’s and society’s attitude.